2020
DOI: 10.3892/etm.2020.9413
|View full text |Cite
|
Sign up to set email alerts
|

Low‑dose X‑ray irradiation induces morphological changes and cytoskeleton reorganization in osteoblasts

Abstract: Recently, research into the biological effects of low dose X-ray irradiation (LDI) has been a focus of interest. Numerous studies have suggested that cells exhibit different responses and biological effects to LDI compared with high doses. Preliminary studies have demonstrated that LDI may promote osteoblast proliferation and differentiation in vitro, thereby accelerating fracture healing in mice. However, the exact mechanism of action by which LDI exerts its effects remains unclear. Previous studies using mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Huang et al examined the alterations in the CSK of osteoblasts after the delivery of 0.5 Gy X-ray radiation [ 89 ]. Notably, the study reported changes in the structure of intracellular actin.…”
Section: Radiation Effects On the Actin Cskmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al examined the alterations in the CSK of osteoblasts after the delivery of 0.5 Gy X-ray radiation [ 89 ]. Notably, the study reported changes in the structure of intracellular actin.…”
Section: Radiation Effects On the Actin Cskmentioning
confidence: 99%
“…Furthermore, the authors investigated the expression of proteins, such as RhoA, ROCK1, and p-cofilin, which stimulate the reorganization of the CSK due to actin depolymerization [ 90 ]. These proteins were involved in the reorganization of the actin filaments after the delivery of radiation, effectively proving that they manage the dynamics behind the regulation of the actin CSK [ 89 ].…”
Section: Radiation Effects On the Actin Cskmentioning
confidence: 99%
“…Concerning mammalian cells several studies report that low‐dose IR (<5 Gy) affects actin‐dynamics leading to reorganization of the actin cytoskeleton (Huang et al, 2020; Huang, Chai, Wang, Sun, & Xu, 2021; Jasinska‐Konior et al, 2019).…”
Section: Actin‐related Ir‐sensitive Yeast Deletion Mutantsmentioning
confidence: 99%
“…11 Cytoskeleton rearrangement is the structural basis for the exchange of intracellular and extracellular information after radiation. 12 The cytoskeleton is mainly composed of actin microfilaments, and provides a mechanical support framework for maintaining cell morphology, and endothelial integrity and repair. 13 The cytoskeleton also plays a vital role in cell adhesion, proliferation, motility, differentiation, division, etc.…”
Section: Introductionmentioning
confidence: 99%